HDAC1 and HDAC2 regulate anti‐inflammatory effects of anesthetic isoflurane in human monocytes. Issue 4 (25th February 2020) - Guo, Xinying; Deng, Jie; Zheng, Bin; Liu, Hao; Zhang, Yuehong; Ying, Yanlu; Jia, Jie; Ruan, Xiangcai
Abstract: Pre‐exposure to volatile anesthetics inhibits inflammation induced by various stimuli, including surgical procedures and ischemia. We hypothesize that volatile anesthetics may induce anti‐inflammatory effects via a mechanism involving regulation of histone deacetylases (HDACs). Pre‐exposure of 1.5% isoflurane for 0.5 h induced anti‐inflammatory effects [measured by cytokine production of tumor necrosis factor‐ɑ, interleukin‐8 (IL‐8) and IL‐1β] in both human THP‐1 cells and primary human peripheral blood monocytes stimulated by lipopolysaccharide. In human THP‐1 cells, coadministration of the HDAC inhibitor trichostatin A (TSA) blocked the isoflurane‐induced anti‐inflammatory effects. TSA also blocked isoflurane‐upregulated HDAC1‒3 expression and isoflurane‐reduced nuclear translocation of p65 and p50 subunits of nuclear factor‐κB (NF‐κB). The ability of isoflurane to reduce NF‐κB nuclear translocation and proinflammatory responses in the cell line was blocked by gene silencing of HDAC1 and HDAC2, but not by gene silencing of HDAC3 . A coimmunoprecipitation assay demonstrated that the decreased interaction between HDAC1 and HDAC2 through lipopolysaccharide was restored by isoflurane pretreatment. These findings were validated in primary human peripheral blood monocytes wherein gene silencing of HDAC1 and HDAC2 resulted in increased cytokine production and NF‐κB nuclear translocation induced by isoflurane pre‐exposure and lipopolysaccharide stimulation. These results indicate that anti‐inflammatory effects of the volatile anesthetic isoflurane in human monocytes involve regulation of HDAC1 and HDAC2. Abstract : In this study, we showed that anti‐inflammatory effects of volatile anesthetic isoflurane involved expression and interaction of histone deacetylase (HDAC) 1 and 2, and were completely inhibited by the coadministration of trichostatin A, a pan‐HDAC inhibitor. Therefore, as an important epigenetic mechanism, histone acetylation modulates the anti‐inflammatory effects of anesthetic isoflurane during inflammation.